Advancing Transnational Corporations’ Overseas Environmental Accountability: The Impact of Mandatory Non-Financial Reporting on Foreign Direct Liability Claims before European National Courts - Barlassina, Silvia (Student Undergraduate Research E-journal!, 2017)
This paper addresses the extraterritorial dimension of transnational corporations, focusing on the corporate accountability-deficit that characterizes the current International legal framework. The analysis looks at parent companies’ civil liability for environmental harm caused abroad. By introducing a selected number of foreign direct liability cases brought before European national courts, the paper investigates whether the binding environmental and human rights reporting obligations contained in Directive 2014/95/EU contribute to the determination of a parent company’s duty of care towards its overseas subsidiaries, and consequently establish their potential liability.